Effects of Watching Cartoons During an Echocardiography on Infants and Preschool Children. A Prospective Randomized Study - Sánchez Ferrer, Francisco; Grima Murcia, M. Dolores; Lopez-Pineda, Adriana; Juste Ruiz, Mercedes; Orozco Beltran, Domingo; Carratala-Munuera, Concepcion; Fernández Jover, Eduardo (Frontiers in Pediatrics, 2019)
Currently the echocardiography is the main diagnostic technique in pediatric cardiology but sometimes it is difficult to apply in children under 3.5 years of age, where cooperation of the patient and the family is necessary to obtain a complete and accurate study. Therefore, the behavior of children is one of the main problems for this procedure, and interventions as sedative medication have been used. The aim of this study was to analyze the influence of TV entertainment in infants and preschool children during echocardiography. We designed an experimental study in children with heart murmur. An examination room was prepared with a TV on the ceiling that was positioned in a way that would provide unobstructed viewing for children during the echocardiography procedure. Fifty-eight patients were randomized into two groups (intervention group with TV or control group with usual care, without TV but with other distraction measures). The primary outcome was echocardiography time, but we also quantified: blood pressure, quality of technique, child behavior and parents stress level. Our results showed a statistically significant reduction in the TV group in terms of less time for echocardiography, less systolic and diastolic blood pressure, better quality of technique and better child behavior. Consequently, we recommend the use of the TV as a simple and useful distraction method for improving the echocardiography in young children.